Variations in Oppel–Kundt Illusion Strength Among Depressive and Schizophrenia Spectrum Disorder Groups: Impact of Benzodiazepine Use - Edgaras Diržius; Rasa Pakanavičiūtė; Deimantė Andriuškevičiūtė; Darius Leskauskas; Aleksandr Bulatov (Medicina)
Background and Objectives: The Oppel–Kundt (O–K) geometric optical illusion has been studied among people with mental disorders to understand the differences in their visual perception. Earlier studies were mainly focused on patients with schizophrenia, while less is known about patients with depression and the influence of medication use. The objectives were to compare illusion manifestation for schizophrenia, depression, and to evaluate possible differences depending on drug use. Materials and Methods: The stimuli consisted of three horizontally arranged dots, which were considered as terminators specifying the ends of the reference and the test stimulus intervals. The reference interval was filled with a set of distracting dots and changed, at random, from 0 to 19. The participants were asked to place the central terminator in the middle, between the outer ones. The trial consisted of 10 different figures, and each trial was repeated 10 times. This study involved 35 patients with depression and schizophrenia spectrum disorders and a comparison group of 35 persons. Information about drug use by patients was retrieved from their medical records. Results: OK illusion manifested stronger in patients with depression compared to the other subjects. The patients who were taking benzodiazepines made greater errors evaluating OK figures than those who were not. No differences were found regarding other drug use. The limitations include a limited sample and possible interfering effects of other drugs, especially antidepressants, which have been shown to affect illusion perception. Conclusions: The OK illusion was more prominent in the patients with depression and in those who were taking benzodiazepines.